The Effect Of Work Discipline On Employee Performance At The Head Office of PT. Prima Karya Manunggal in Pangkep Regency - Saputri, Suci Ramadhani; Haris, Hasnawi; Baharuddin, Aris; Syarifuddin, Syarifuddin (Universitas Negeri Makassar, 2025)
This study aims to find out how the influence of work discipline on employee performance at the Head Office of PT. Prima Karya Manunggal in Pangkep Regency. This research uses quantitative research methods. The data collection technique carried out is through observation, questionnaires and documentation. In this study, the sample technique used was a sampling technique. saturation of 53 respondents of PT Head Office employees. Prima Karya Manunggal in PangkepRegency. The data analysis techniques used are validity and reliability tests to test the feasibility of questionnaires, descriptive analysis, normality tests, simple linear regression tests to test hypotheses and product moment correlation tests to test the presence or absence of significant relationships and how much influence work discipline has on employee performance. The results showed that: (1) Dsiplin works at the Head Office of PT. Prima Karya Manunggal in PangkepRegency is in the good category in terms of attendance frequency, level of vigilance, strictness on work standards, compliance with work regulations, and work ethics. (2) Performance of employees at the Head Office of PT. Prima Karya Manunggal in Pangkep Regency is in the good category in terms of work quality, quantity of work, implementation of duties and responsibilities. (3) 62.4% of the effect of work discipline on performance at the Head Office of PT. Prima Karya Manunggal in Pangkep Regency.